New quality and quantity indices in science (NewQIS): results of the first decade—project progress review - Groneberg, David A. (Scientometrics, 2019)
Strategies employing information science and scientometric approaches were introduced to science policy and management over the past decades. As a rapidly evolving field, new bibliometric parameters are proposed and discussed continuously and the fields also benefits from the introduction of novel visualization techniques. The present article summarizes the experiences with a platform that combines geographical mapping with scientometrics. It was established between 2005 and 2008 at the Charité in Berlin and termed “New Quality and Quantity Indices in Science” (NewQIS), consisting of the integration of common scientometric parameters such as the h-index and novel visualization techniques including density equalizing mapping. NewQIS was used to assess socio-economic important fields of medicine and sciences. Within NewQIS studies, research activities, citation patterns and their relation to socio-economic figures were analyzed with regard to time periods, countries, continents or even single cities. Within the decade after its establishment, more than 80 NewQIS articles were peer-reviewed and published. Being a non-funded low budget project, it was used by many medical students to conduct their MD thesis. The narrow technical frame led to the chance of a comparison of research output between different fields of science. This article summarizes NewQIS 1.0 activities, discusses its limits and gives a look into the future of NewQIS 2.0 with a target of 200 evaluated entities of the biomedical field of sciences.